Does Reward System Effect Employee Job Satisfaction: Evidence from Public Sector - Zulkifli Musannip Efendi Siregar; Marihot Marihot; Ikhwanuddin Lubis (Garuda Prestasi Nusantara Consulting, 2023)
Job satisfaction is one of the most important issues for employees. High job satisfaction will make employees have higher work productivity. Research examines the reward system as an antecedent variable that affects employee job satisfaction. The research was conducted with a quantitative approach. The sample in this study were agricultural extension workers at the Labuhanbatu District Agriculture Office. Until the research as many as 38 respondents. The data analysis technique was carried out by SEM Smart PLS. The results of the study show that it is proven that the reward system can have an influence on increasing employee job satisfaction at work. Keywords: Reward System, Job Satisfaction